2014
DOI: 10.1097/ncc.0b013e318277dc53
|View full text |Cite
|
Sign up to set email alerts
|

Factors Relating to Quality of Life After Esophagectomy for Cancer Patients in Taiwan

Abstract: Knowledge of risk factors for poor postoperative QoL would be useful for health providers in detecting and prioritizing problems and treatment options in a busy clinical site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 29 publications
2
22
1
Order By: Relevance
“…Similarly, Seo-in Ha et al found that dysphagia was one of the most common symptoms affecting the HR-QoL of patients with esophageal cancer [34]. Unlike a previous study, we found that as the disease worsened, HR-QoL areas of dry mouth and trouble with taste remained constant (i.e., no signi cant difference) [35]. We also found that the most severe symptom was re ux, which agrees with a previous study on HR-QoL in patients after esophageal cancer surgery [36].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Similarly, Seo-in Ha et al found that dysphagia was one of the most common symptoms affecting the HR-QoL of patients with esophageal cancer [34]. Unlike a previous study, we found that as the disease worsened, HR-QoL areas of dry mouth and trouble with taste remained constant (i.e., no signi cant difference) [35]. We also found that the most severe symptom was re ux, which agrees with a previous study on HR-QoL in patients after esophageal cancer surgery [36].…”
Section: Discussioncontrasting
confidence: 60%
“…Results from the EORTC QLQ-OES18 module revealed that the pathological stage had greater effects on symptom scales, and other factors had little effects on those scales. In this regard, Yu-Ling Chang showed that advanced tumor stage had signi cant deleterious effects on several aspects of HR-QoL, such as eating di culties, and there were no associations between any factors (age, gender and body weight loss) and esophageal-speci c aspects of HR-QoL [35]. Therefore, it is important to carry out early diagnosis and treatment program and to conduct follow-up care since those patients with advanced cancer usually have worse HR-QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Far more surprisingly, the diseased organ did not influence compliance, as one could imagine that patients suffering from upper GI pathology would be prone to difficulties in consuming nutritional products, because of the impaired transit or swallow mechanisms. [19][20][21][22] Caloric excess was observed significantly more often in compliant patients, reflecting the important influence of ONS on caloric balance. Assessment of the degree of malnutrition by hospital's nutritionists did not correlate with compliance to nutritional regimens.…”
Section: Discussionmentioning
confidence: 96%
“…Tongue pressure is one of the important parameters for evaluating a swallowing disorder, which is a prominent symptom after esophagectomy and may cause aspiration pneumonia [2]. Complications, including pneumonia, affect patients' quality of life and survival [7,21,22]. Thus, these findings suggest that we should pay attention to tongue pressure, especially to high level of preoperative tongue pressure in patients with esophageal cancer after esophagectomy.…”
Section: Discussionmentioning
confidence: 99%